A common environment experiment reveals plastic and genetic contributions to the fast life‐history strategy of an invasive fish. Issue 4 (1st July 2018) - Rooke, Anna C.; Fox, Michael G.
Abstract: Invasive species often exhibit a suite of life‐history traits that promote rapid population growth, including early age and small size at maturation, and high reproductive investment. The common expression of these "fast" life‐history traits in invasive populations could be the result of plastic and/or genetic responses to the non‐native environment, or in response to the process of range expansion. To determine the relative importance of plastic and genetic contributions to the expression of life‐history traits, we reared two native Canadian and two invasive Spanish populations of Pumpkinseed sunfish ( Lepomis gibbosus ) in a common environment in central Ontario, Canada. In the wild, European Pumpkinseed tend to exhibit faster juvenile growth rates, younger age and smaller size at maturity, and higher reproductive investment than native North American populations. When reared in a common environment, both native and invasive populations exhibited similar juvenile growth rates, and similar age and size at maturity, suggesting that the differences seen among wild populations are a plastic response to the warmer non‐native environment. However, reproductive investment was consistently higher in the Spanish populations regardless of rearing environment, suggesting a genetic difference in reproductive investment between native and invasive populations. Selection for greater reproductive investment in non‐native Pumpkinseed may have contributed to their widespread success in Europe.